Türkiye'de Yolsuzluğun Nedenleri-Ekonometrik Bir Inceleme - Guzin Bayar (Turkish Economic Association, 2007)
– Corruption is seen in nearly every society since ancient times. However, economic and social costs it caused attracted more attention especially in the last decade. It is widely agreed upon that, corruption affects economic growth and development negatively. In the literature, there is almost a consensus about that corruption of the public officers discourages entrepreneurs, causes inefficiencies and waste of resources, discourages foreign investment, distorts income distribution and harms democracy and ethics. Putting the diagnosis truly and knowing the deep causes of a problem correctly are the most important steps in solving the problem. In this article, first, a survey of the literature on costs of corruption, measurement methods ve causes is given. Then regression analysis are done to find probable causes of corruption in Turkey. Results of the regression analysis show that, corruption has increased in Turkey after trade liberalization. On the otherhand, inflation, weight of pubic in the economy and personel expenditures of the government seems not to be important factors in explaining corruption.
Keywords: 330; Corruption; measurement; regression; opening up; Korruption; Türkei